Strategic Reconciliation Based on Islamic Principles in the Israel-Palestine Conflict - Soim, Moh; Mohammad Ulil Rosyad (Tashwirul Afkar, 2023)
This study explores the strategic reconciliation framework proposed by Ahmad Umar Hasyim, rooted in Islamic principles and its potential application in resolving the Israel-Palestine conflict. The research investigates how Hasyim’s ethical and spiritual approach can complement existing political and legal frameworks to achieve sustainable peace. The research employs a qualitative approach, combining descriptive analysis and historical methods to examine the relevance of Hasyim’s reconciliation strategies. Thematic analysis is applied to identify recurring concepts, such as internal and external peace, human rights, societal harmony, and the preservation of life. The study finds that Hasyim’s reconciliation strategy offers a unique perspective by integrating spiritual and ethical principles into the peace process. His emphasis on human dignity, social justice, and the sanctity of life provides a comprehensive approach that addresses both the political and moral dimensions of the Israel-Palestine conflict. This research contributes to the broader literature on peacebuilding by highlighting the potential role of religious diplomacy in conflict resolution. It suggests that integrating religious values into diplomatic efforts could enhance the effectiveness of existing peace strategies, particularly in conflicts involving deep-rooted religious identities. This study provides an innovative approach by focusing on Islamic principles as a foundation for reconciliation in the Israel-Palestine conflict. It offers a new perspective on how religious frameworks can contribute to international peace efforts, a topic that has been underexplored in previous research.